The Pendidikan Lingkungan Hidup sebagai Upaya Konservasi di Kawasan Wisata Gedong Songo - Desti Cahyaningrum; Andreas Binar Aji Sukmana; Rully Adi Nugroho (Universitas Lancang Kuning, 2021)
Gedong Songo is a National Tourism Development Area in Bandungan region with an increasing number of visitors. Previous studies found that littering and water pollution were some of the prominent problems in Gedong Songo. The lack of knowledge and awareness towards environmental management was identified as the center of the issues. A conservation effort in the form of an early environmental education targeted elementary school students was suggested to address this problem. The environmental education was performed in State Elementary School Candi 1 and Candi 3 Bandungan and was designed as a series of activities, including lectures, discussions, observations, as well as experimental activities. As a result, many students were found to be actively engaged throughout the activities and showed an improved attitude. They realized the importance of washing hands, keeping environmental hygiene, and problem-solving. Further evaluation indicated that the students had developed a better understanding of general environmental management. Therefore, it can be concluded that early environmental education can potentially transform students' knowledge and awareness about the importance of environmental conservation. Through these activities, it is expected that the obtained experiences will support the Gedong Songo environmental conservation in the future.